When Athena met Tim the Toolman: connecting Organisational Learning and information systems. (19th April 2004) - Hendriks, Paul H.J.
The notion of organisational learning (OL) aims to introduce a broad perspective on how an organisation as a whole perceives the interplay with its competitive environment and handles it. Although the role of Information Systems (IS) in relation to OL has been assessed by several authors, most of these assessments have not adopted an equally broad perspective on the role of ISs. A framework is needed to express the broad organisational concept envisaged in the notion of OL, and to provide the pegs to link ISs to OL accordingly. Such a framework for valuing ISs in relation to OL is proposed and elaborated. A case study of the relationship between Geographical Information Systems and Organisational Learning in an environmental consultancy firm is presented to illustrate the contents and application of the framework.